Analysis of autocorrelation based frequency measurement algorithm for IFM receivers - Darvin, R. Charles; Paranjape, Hemant; Mohanan, Sarath Kundumattathil; Elango, Venkatesh (2014 IEEE International Conference on Electronics, Computing and Communication Technologies (CONECCT), 2014)
The instantaneous frequency estimation of received signal is very important in Electronic Warfare and communication systems, and the performance of radar classification depends on the accuracy of frequency measurements. Hence, different approaches to the instantaneous measurement of the frequency of a radio wave signal are proposed and analysed. The auto-correlation factor based algorithm is optimised to estimate the signal frequency more accurately. The algorithm is also able to estimate the maximum error in the estimated frequency for any input frequency. Simulation results ascertain the robustness of the algorithm and confirm that it is not affected by clock jitter and is capable of detecting pulses from 100 ns width and SNR ≥ 0 dB, over a 4 GHz bandwidth. For SNR ≥ 20 dB, the algorithm is able to estimate 99.4% of the frequencies in the 4 GHz bandwidth within an error of 2 MHz. This algorithm has the potential to be coded and ported on to a Field Programmable Gate Array.